Comparison of Students' Speaking Anxiety based on Students' Learning Style - Yola Angela; Havid Ardi (Journal of English Language Teaching, 2022)
The aim of this research is to compare the students’ speaking anxiety based on students’ learning style at second grade of SMP N 29 Padang. It was carried out using descriptive method. In learning style, the result of this research showed almost of 31 students in class VIII.1 of SMP N 29 Padang dominant in “Authority- Oriented” after that they dominant in “Concrete”, and just several students who dominant in “Communicative” learning style. Furthermore, based on speaking anxiety level, the result of this research showed almost of all students in class VIII.1 of SMP N 29 Padang dominant in “Anxious” level in the first position and in second position the students dominant in “Mildly Anxious” , but just several students who dominant in “relaxed” speaking anxiety level.